Ways of Seeing Nujoom Alghanem’s Nearby Sky (سماء قريبة) and Sharp Tools (آلات حادة) as Docupoetry - Hambuch, Doris (Imaginations)

(untitled) (York University, 2024)
This article proposes to establish a sub-category called “docupoetry” to classify the documentary films by Emirati poet and filmmaker Nujoom Alghanem. Detailed analysis of two selected films, Sharp Tools (2017) and Nearby Sky (2014), illustrates the unique composition, cinematography, and use of poetic devices, such as rhythm, symbolism, and personification of settings, which render the proposed classification beneficial for viewers. Based on Michael Renov’s concept of the poetic documentary as well as on the poetic mode theorized by Bill Nichols, this study finds the definition of a separate sub-category warranted to understand documentaries such as those by Alghanem.